Fitoperifiton de un lago somero y su relación con los estados de biequilibrio - Cano, María Gabriela (2009)
The role of communities associated to a substrate as fundamental components of an aquatic system has been recognized by many authors. Although periphyton has been considered of great importance in shallow lakes, its inclusion in different ecological models has been unusual. Phillips et al. (1978) were the first in considering epiphyton as an internal mechanism leading the system to a change in its state from greater water transparecy to more turbid conditions. In contrast, Scheffer et al. (1993) proposed the Alternative Equilibria Hypothesis (AEH), which considers that a shallow lake can alternate between two states, a Clear Water State (stabilized by the presence of submerged macrophytes) and a Turbid Water State (stabilized by an elevated phytoplankton biomass), excluding in this scheme the periphytic communities. Later only the conceptual model coined by Goldsborough and Robinson (1996, G&R model) emphasizes again the importance of epiphyton as well as that of epipelon and metaphyton by establishing the possibility of occurrence of four states according to the contributions to the total algal biomass of each of the algal taxocenosis. Some analyses of the system’s dynamics have been performed in pampean lakes in the context of the AEH. On the other hand, knowledge regarding periphytic and benthic communities is still poor. We propose as an hypothesis that phytoperiphyton will respond to the occurrence of different equilibria states, displaying, at the same time, strong interrelationships with the phytobenthos as well as with the phytoplankton. On the other hand, we consider the possibility that the phytoperiphytic and phytobenthic assemblages may function as internal mechanisms both, as state change or as state stability factors. Finally, we assess the importance of phytoperiphyton as regards its contributions to the total algal biomass in the context of the G&R model, comparing then the results with those obtained in the case of the AEH. The general objectives of the present investigation are to gather information about the structure and dynamics of the phytoperiphyton and its relationships with environmental factors as well as with the phytobenthon and phytoplankton in a pampean shallow lake; and to analyze phytoperiphytic dynamics under the AEH and the G&R model contexts, evaluating periphytic contributions to the total algal biomass. This investigation was carried out in an seepage shallow lake, Lacombe Lake, which is included in the “Grupo Marginal de lagunas” group in the pericoastal region of Provincia de Buenos Aires. Sampling was performed from July 2001 to June 2002 at four sites according to their exposure to environmental factors and the presence of macrophytes: bulrush beds, (JP and JC); and sites devoided of emergent vegetation but with stands of submerged macrophytes during the growing season (ALe and ALr). J sites and ALe were also representative of deeper zones and ALr of a site near the shore. Environmental variables were measured in situ and water samples were collected for chemical analysis and for plankton identification and quantification, following a vertical profile (excepting in ALr). In the case of phytoperiphyton, bulrush epiphyte samples (epiphyton) were taken following a vertical profile and those of submerged macrophytes were collected from the first 25 cm of the stems. Benthon (epipelon) was sampled using a corer. Aliquots for chemical analysis were also extracted from those samples. Vegetal substrate dynamics was also evaluated during sampling. At the laboratory, concentrations of algal nutrients, of the eight principal ions and of soluble polyphenols, as well as alkalinity and total hardness were measured. Phytoplanktonic, epiphytic and epipelic samples were treated for active a chlorophyll and pheopigment determinations. Organism identification and quantification were made according to standardized and own developed methods. First, variations in biotic and abiotic variables were analyzed for the determination of different equilibrium states occurrence. Three perturbation events were registered: precipitations in August, October and March. All of them involved water level increases and conductivity diminutions. Especially in the first two events, nutrient input from runoff was observed; meanwhile in March the input of water determined the dilution in nutrients concentrations. On the other hand, light conditions improved, particularly from October onwards, when stands of submerged macrophytes developed and a decrease of phytoplankton density and a change in its specific composition was detected. The latter being generated by the dilution effects of water input, the shading of the aquatic plants and algal consumption by cladocerans. March event also involved an improvement of light underwater climate but the increase in the water level affected macrophyte stands which mainly withdrawed to the shallowest zones. As regards phytoplankton, changes in the specific composition were recorded again. The statistic evaluation of these facts in conjunction with the analysis of permanence, resiliency and resistance properties of the dominating taxocenosis leads to interpret in the context of the AEH that two equilibria states occurred in the shallow lake. During the first three months a Turbid Water State developed, given by the phytoplankton domination given by an oscilatorial cyanophyte, minor transparency and relatively higher nutrient concentrations. In October and November the passage between states occurred, thus considering these months as transitional. From December onwards a Clear Water State established given by extended development of stands of submerged macrophytes, greater water transparency and minor nutrient concentrations. Finally, from March to May, given the submerged macrophyte withdrawal to shallowest sectors it can be interpreted that the system oscillated around a clear water state, or else, taking into account changes in the planktonic community, it is suggested that a third different state established, the “mixed phytoplankton” state. It is also suggested that states developed in Lacombe could be alternative. Next, the structure and dynamics of phytoperiphyton on bulrush and submerged macrophytes was analyzed. Vertical spatial and temporal variations of bulrush epiphyton showed to be more important than differences between sites. These variations involved smaller biomass values and a simpler physiognomy during turbid water phase and along the vertical gradient in all sampling occasions. In October, related to better light underwater conditions and the nutrient input, epiphytic biomass increased, principally promoted by species typical of the turbid phase. Nonetheless, a structural change started in this month, driven by herbivores but also by the modification of internal relationships between members of the same taxocenosis (shading and less bare substrate to be colonized). This resulted in the establishment of the characteristic assemblages of the clear water phase. During the first three months domination by stalked diatoms structured the community in a unique stratum, resistant to the less favourable light conditions and resilient to August perturbations. From December onwards Spirogyra species dominated, constituting the upper stratum, followed by Oedogonium species in the middle stratum and diatoms in the lower one. These assemblages were stabilized by mechanisms mainly displayed by the zignematalean taxon (shading, epifitism inhibition), allowing to considerer that they were resilient to March perturbation event (de novo establishment on non previously colonized surfaces). In face of the permanence, resistance and resilience properties showed by the taxocenosis, two different states of bulrush phytoperiphyton are considered: turbid water and clear water assemblages. This temporal pattern appeared less well delimited with depth and showed up later in time. Epiphyton data suggested that both states could be alternative. Differences between sites could be observed in respect to phytoperiphyton growing on submerged macrophytes, but the same temporal pattern showed by bulrush periphyton couldn’t be detected due to a great variability in the data gathered. In the next section, the analysis of the structure and dynamics of the phytobenton was carried out. It was showed that differences between the deepest sampling points and the shallowest site were greater than temporal ones. The composition of the assemblages was scarcely variable in time. The taxocenosis was principally related to the poor light conditions recorded on the sediment surface throughout the entire sampling period, even during the clear water phase. The examination of the specific composition in function of its origin evidenced the influence that the epipelon receives from other taxocenosis, constituting a refuge site for allochthonous taxa during unfavourable situations. The scarce variability of the epipelic fraction is also showed. In this way, it is considered that the taxocenosis maintained itself in only one state, indifferent to state changes in the lake and principally resisting the darkness and bearing to live in the unstable sediments. Subsequently, first the roles of the phytoperiphyton and complementary those of phytobenton, as state change or state stability agents were evaluated. The harmful effect of the phytoperiphyton on submerged macrophytes was probably counteracted by plant ramification production and allelopathy. The evidence suggested that its role as nutrient sequestrator is of minor importance in this case, due to other factors that might have disturbed phytoplankton more intensely than competition with phytoperiphyton. Much evidence supported the role of phytobenton as a source of epiphytic and planktonic species belonging either to turbid and clear water state assemblages. The results did not support the hypothesis that phytobenton may play a role as a sediment-stabilizing factor. On the contrary, it may be perturbating agent. Next, an analysis of the contributions of each community to the total algal biomass in the context of the G&R model was performed. Comparisons with AEH results were also carried out. This leaded to the consideration of the occurrence of the following states in Lacombe Lake: a Lake State consistent with the Turbid Water phase, an Open State consistent with the Clear Water phase and local Dry States in ALr site occurred both during the turbid water phase (July) or the clear water situation (March-April). The substantial contribution of epiphyton especially, that growing on submerged macrophytes, is emphasized. The importance of the discrimination of different fractions of epipelon material according to its origin when evaluating the contributions of each community to total algal biomass is also highlighted. Finally, a new interpretation is presented based on algal taxocenosis dynamics, which incorporates elements from both, the AEH and the G&R model. In conclusion, phytoperiphyton in this pampean shallow lake is strongly affected by the factors that determine the establishment or passage from one equilibrium state to another. These assemblages respond to changes through modifications in their own internal structure. These structures gradually alter with depth, remaining these changes more fully explained by the comparison with phytobenton dynamics. Besides the possible roles that the taxocenosis might undertake as an internal mechanism in the change or stabilization of systems states in different situations other than those encountered during this study, epiphyton importance in the systems context, is principally evidenced by the great contribution that these taxocenosis make to the total algal biomass, constituting the dominant compartment during clear water states.